A Systematic Mapping of the Literature about Tools for Data Validation in Business Rules Tests - Silva, Nathalia Rezende; Costa, Heitor A. X.; Parreira Júnior, Paulo Afonso (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
With the increasing use of Information Systems (IS), increasingly complex and robust, the concern with the tests carried out during its development became prominent. Data validation, part of the business rules tests, focuses on detecting defects and inconsistencies in the system data and is a process of paramount importance for the company that maintains the IS, since incorrect data can lead to economic and even legal problems. However, manual execution is a lengthy and difficult to replicate process, of limited sample size. Therefore, the objective of this work was to perform a Systematic Literature Mapping (SLM), with the purpose of identifying, classifying and cataloging existing computational supports in the literature, which allow the automation of the data validation process. With the implementation of the SLM, 6 studies were accepted and analyzed, and after reading in full of each of them, 5 possible tools for automation of data validation were identified. Finally, it was verified that different approaches are used in each tool and the choice of each one depends primarily on the scenario and characteristics of the company and project under development. In addition, there is a shortage of studies on the subject, making it an area to be explored.